Pipelines for lymphocyte homeostasis maintenance during cancer immunotherapy - Du, Bensu; Geng, Jin; Wu, Bin; Wang, Houru; Luo, Ru; Liu, Hanmeng; Zhang, Rui; Shan, Fengping; Liu, Lei; Zhang, Shuling (Frontiers in Immunology, 2025)
In general, increasing lymphocyte entry into tumor microenvironment (TME) and limiting their efflux will have a positive effect on the efficacy of immunotherapy. Current studies suggest maintenance lymphocyte homeostasis during cancer immunotherapy through the two pipelines tumor-associated high endothelial venules and lymphatic vessels. Tumor-associated high endothelial venules (TA-HEVs) play a key role in cancer immunotherapy through facilitating lymphocyte trafficking to the tumor. While tumor-associated lymphatic vessels, in contrast, may promote the egress of lymphocytes and restrict their function. Therefore, the two traffic control points might be potential to maintain lymphocyte homeostasis in cancer during immunotherapy. Herein, we highlight the unexpected roles of lymphocyte circulation regulated by the two gateways for through reviewing the biological characters and functions of TA-HEVs and tumor-associated lymphatic vessels in the entry, positioning and exit of lymphocyte cells in TME during anti-tumor immunity.